Islamic Family Counseling Through Digital Media as an Effort to Overcome the Moral Crisis of Muslim Youth in the Era of Information Disruption - Rahmaliyah Ningrum, Dinda; Mutiara Sani, Amanda (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
The era of information disruption, marked by the rapid development of digital technology, has triggered a moral crisis among Muslim teenagers. This study aims to determine the role of Islamic family counseling in addressing moral crisis issues among Muslim youth in the era of information disruption. It uses a qualitative method with a literature review approach. Data collection was conducted by reviewing relevant books, journals, and scientific articles. Data analysis used the Miles and Huberman model. The results showed that digital-based Islamic family counseling is effective in guiding adolescents to have good character. This counseling utilizes digital media to increase the flexibility and reach of services, despite facing challenges such as privacy and digital literacy issues. Therefore, supporting strategies are needed, such as improving counselor competence and developing digital ethics guidelines. In conclusion, digital Islamic family counseling is an appropriate way to guide adolescents in the modern era so that they can filter information and have strong morals.